The juniper bush of autism spectrum disorder (ASD): metabolomics, microbiomics, acetaminophen. What else? - Fanos, Vassilios; Noto, Antonio; Mussap, Michele (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2018)
In the United States, a very recent survey performed on children aged 8 years assessed an overall prevalence of 16.8 autistic children every 1,000 non-ASD children (equal to 1 child every 59), with a higher prevalence in boys (26.6 per 1,000) than in girls (6.6 per 1,000). Actually, very few human diseases like ASD can be considered the result of interplay between a multitude of factors: genetics, epigenetics, environment, socioeconomic status, maternal and neonatal infections, prenatal nutrients (i.e. folic acid), immune system, gut microbiota composition, maternal exposure to potentially toxic drugs (e.g. thalidomide) and environmental toxicants, and formula feeding (instead of breastfeeding). Taken individually, each of these factors may be considered a potential risk factor for developing ASD. However, the wide range of symptoms and disabilities depicting ASD as a “galaxy of social and communication difficulties” takes place through the combination of two or more factors cited above; notably, the role of each (e.g. genetics) cannot be dissociated from the context of epigenetic mechanisms and specific interactions. Today, we can accurately explore the metabolome and its variations over time in various perinatal conditions involved in ASD etiology, for example perturbations of the gut-brain axis, due to gut dysbiosis, and to the lack of the intestinal mucosal barrier, caused by inflammation. This means a great opportunity to establish an early diagnosis of ASD, to assess the risk of developing postnatal ASD and to search for new highly sensitive and specific biomarkers especially in urine. Most of the performed studies have found abnormalities in gut bacterial-derived compounds, tryptophan, vitamin B6, and purine metabolic pathways, phenylalanine and tyrosine biosynthesis, unbalanced concentration of intermediary compounds of the tricarboxylic acid cycle (TCA), also known as the citric-acid or Krebs cycle, and finally diet-derived metabolites. By using 1H NMR spectroscopy, our group found a combination of increased and decreased concentrations of: hippurate, glycine, creatine, tryptophan, D-threitol, and glutamate, creatinine, lactate, valine, betaine, and taurine, respectively. These findings strongly suggest a crucial role of oxidative stress and gut microflora in ASD development. In children with ASD, gut dysbiosis is characterized by the increase in Clostridium, Alistipes, Akkermansia, Caloramator, Sarcina spp., and by the reduction in Prevotella spp., E. siraeum, and Bifidobacterium spp. As a result, in these children the urine metabolome is marked by alterations in hippuric acid, p-hydroxyphenylacetic acid and 3-(3-hydroxyphenyl)-3-hydroxypropanoic acid concentration. Moreover, propionic acid, related to Clostridium spp. is strongly involved. Metabolomics can lead to the discovery of dozens of biomarkers strongly implicated in the pathogenesis of ASD (i.e. mannitol, L-threonic acid, fucose, glycine, serine, and many others). Finally, the potential toxicity of acetaminophen (paracetamol), a very common analgesic and antipyretic drug widely used during pregnancy, after birth and in early childhood should be carefully considered in combination with the microbiome.